Edukasi Tata Kelola Keuangan Pribadi Melalui Pemanfaatan Fintech Pada Siswa Smks Assa Adatul Abadiyah Bekasi - Kiko Armenita Julito; Sihar Tambun; Lukiyana Lukiyana; Robiur Rahmat Putra; Donny Syahputra (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
The use of fintech is increasingly trending among society, especially in the millennial and generation Z age groups. This generation needs to be educated about the smart use of fintech. Students at SMKS Assa Adatul Abadiyah, located in Muara Gembong, Bekasi, need education about personal financial management through the use of fintech. This community service program is carried out with the aim of improving personal financial management capabilities, through the intelligent use of fintech. This community service activity is carried out using an Asset Based Community Development approach. The method used is lecture and question and answer discussion. The results include three things. First, participants experienced an increased understanding of various types of fintech and their facilities. Second, participants increasingly understand the use of fintech to support financial planning. Third, participants increasingly master various financial management tips. This community service activity program has succeeded in improving personal financial management skills, through smart use of fintech